Uma análise do desenvolvimento dos níveis do pensamento geométrico segundo o modelo de Van Hiele dos alunos do 9° ano de uma escola pública no bairro Aviação em Abaetetuba-PA - SENA, Regina Maciel (2019)
Considering that geometry is present in almost all places where we are and often goes completely unnoticed its teaching becomes indispensable in school curricula. Based on this assumption and having as theoretical foundation the Van Hiele model where it says that the process of the development of geometric thinking is based on five levels of understanding and five stages of learning to progress between these levels, the present study builds its bases in the orientations described by Van Hiele for the teaching of geometry, where its purpose is to report a practice performed with students of the 9th grade of elementary school of a public school in the city of Abaetetuba - PA. It is a qualitative research that aimed to investigate and detect, through the Van Hiele Theory, the level of geometric thinking of the learners, where the Van Hiele test was proposed, respecting the characteristics, properties and phases of each level of learning. As a conclusion the research reveals the difficulties that students face when content and geometry indicates that there is an absence of Geometry teaching since the early years and that this absence can be attributed to several factors, some even related to teacher training. Therefore the need for a deeper understanding of the teaching of geometry.